1980
DOI: 10.1530/acta.0.0930228
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conception on the concentration of urinary oestrone-3-glucuronide, LH/hCG and pregnanediol-3α-glucuronide

Abstract: The concentrations of oestrone-3-glucuronide, LH/hCG and pregnanediol-3\g=a\-glucuronide have been measured in daily samples of early morning urine from 6 women throughout the normal ovarian cycle and from 5 subjects, who conceived during the period of study. In addition, the ratio of oestrone to pregnanediol glucuronide was calculate as an additional index of ovarian function.The results showed that the ratio during the follicular phase of the cycle was similar in both groups of women. Moreover, there was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 2 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…We also found that E 1 C increased 13-16 days after fertilization, and remained elevated until parturition or abortion. The results of this study confirm that estrone glucuronide concentrations reflect ovulation and implantation in primates [Branch et al, 1980]. PdG is an abundant urinary metabolite of progesterone that has been studied in primate species, including humans, great apes, gibbons, baboons, langurs, and certain Macaca Hodges et al, 1986;Nadler et al, 1993;Thierry et al, 1996].…”
Section: Discussionsupporting
confidence: 75%
“…We also found that E 1 C increased 13-16 days after fertilization, and remained elevated until parturition or abortion. The results of this study confirm that estrone glucuronide concentrations reflect ovulation and implantation in primates [Branch et al, 1980]. PdG is an abundant urinary metabolite of progesterone that has been studied in primate species, including humans, great apes, gibbons, baboons, langurs, and certain Macaca Hodges et al, 1986;Nadler et al, 1993;Thierry et al, 1996].…”
Section: Discussionsupporting
confidence: 75%
“…Concentrations increase very early in gestation, decline in the fourth or fifth week after implantation, and then increase as the placenta becomes the primary source of progesterone [14,15]. However, there are few data on change in progesterone levels around the time of implantation, data that would reflect the time of CL rescue [16][17][18]. The largest sample of pregnancies for which such data were recorded was presented by Lenton and Woodward [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is usually recommended that a pregnancy test should be performed on the first urine specimen passed after the woman wakes in the morning. Most clinical studies involving the measurement or urinary human chorionic gonadotrophin (hCG) have used early morning specimens of urine (Banik & Givner 1979; Branch et al 1980; Wang & Gemzell 1982; Baker, Kovack & Burger 1987; Asch et al 1988). Because various other solutes are at high concentrations in this specimen, it is assumed that hCG concentrations will also be relatively higher and, therefore, more likely to yield a positive result.…”
mentioning
confidence: 99%